1997
DOI: 10.1172/jci119728
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of tumor necrosis factor-alpha gene by Epstein-Barr virus and activation of macrophages in Epstein-Barr virus-infected T cells in the pathogenesis of hemophagocytic syndrome.

Abstract: A potentially fatal hemophagocytic syndrome has been noted in patients with malignant lymphomas, particularly in EBV-infected T cell lymphoma. Cytokines, such as interferon-␥ (IFN-␥ ), TNF-␣ , and IL-1 ␣ , are elevated in patients' sera. To verify whether infection of T cells by EBV will upregulate specific cytokine genes and subsequently activate macrophages leading to hemophagocytic syndrome, we studied the transcripts of TNF-␣ , IFN-␥ , and IL-1 ␣ in EBV-infected and EBV-negative lymphoma tissues. By revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(173 citation statements)
references
References 41 publications
(62 reference statements)
9
159
1
1
Order By: Relevance
“…7,29,30 These findings suggested to us that the EBV-infected T cells may survive or even proliferate in the cytokine milieu of HPS, in which TNF-␣ is presumed to be the culprit cytokine. 8 Consistent with previous studies, 26 we demonstrated here that EBV LMP-1 could up-regulate TNF-␣ via a TRAFs/NF-B pathway in EBV-infected T cells. Importantly, LMP-1-expressing T cells could escape and survive from TNF-␣-induced apoptosis through down-regulation of TNFR1, providing a potential mechanism to explain the relapsing or progression to T-cell lymphoma in HPS patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…7,29,30 These findings suggested to us that the EBV-infected T cells may survive or even proliferate in the cytokine milieu of HPS, in which TNF-␣ is presumed to be the culprit cytokine. 8 Consistent with previous studies, 26 we demonstrated here that EBV LMP-1 could up-regulate TNF-␣ via a TRAFs/NF-B pathway in EBV-infected T cells. Importantly, LMP-1-expressing T cells could escape and survive from TNF-␣-induced apoptosis through down-regulation of TNFR1, providing a potential mechanism to explain the relapsing or progression to T-cell lymphoma in HPS patients.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3][4] Distinct from other EBV-associated disorders, the infection of T cells by EBV may manifest a fatal form of infectious mononucleosis or hemophagocytic syndrome (HPS) in young children, characterized by hepatosplenomegaly, pancytopenia, coagulopathy, and a systemic proliferation of T cells and macrophages with enhanced cytokine secretion, particularly tumor necrosis factor-␣ (TNF-␣) and interferon-␥. [5][6][7][8] The enhanced cytokine secretion has been presumed to play a key role in the pathology of HPS, which includes apoptosis and deple-tion of the immune system and the impairment of hepatic and pulmonary functions. 9 -11 TNF-␣ may induce apoptosis and cell injuries via binding to TNF-␣ receptor-1 (TNFR1) to activate the TRAF2/TRADD/FADD (TNFR-associated factor 2/TNFR1-associated death domain/Fasassociated DD) signaling and caspase activities.…”
Section: The Infection Of T Cells By Epstein-barr Virus (Ebv) May Resmentioning
confidence: 99%
See 1 more Smart Citation
“…They secrete many inflammatory mediators and proinflammatory cytokines such as IL-1, IL-6, TNF-␣, IL-12, and IL-18 (12,31). IL-12 and IL-18, which share many common functions in innate and acquired immunity, exhibit a marked synergism in activating T cells and NK cells (11,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of interferon-λ, tumor necrosis factor-α, interleukin-1, 6 and soluble interleukin-2 produced by T cells have been demonstrated in HLH [11]. Although T cells lack CD21 receptor for the EBV entrance into the cells, EBV genome was present in T cell lymphomas and T lymphocytes from patients with HLH [12,13]. EBV driven T cell and NK-cell lymphomas are among the most common lymphoid neoplasms associated with the development of HLH [14].…”
Section: Or At Least 3 Ofmentioning
confidence: 99%